(untitled) (TAMADDUN NURI JURNALI, 2024)
The article is devoted to the scientific substantiation of the method of “contextual associative translation (CAT)” of homonyms with an emphasis on Uzbek and English literature. The CAT method is an advanced approach to resolving lexical ambiguities, where the key aspect is a deep understanding of the context and associative connections in the text. The article analyzes examples from Uzbek and English literary works, demonstrating how the СAT method allows for accurate interpretation of homonyms, preserving the original semantic and cultural nuances.